1886 Md. Laws 315, ch 189, § 1 - (:unkn) unknown (General Publisher, 1886)
Prohibited the carrying of a gun, pistol, dirk, dirk-knife, razor, billy or bludgeon on an election day. Punishable by a fine of $10-50.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES